Frequency of Expression of BRAF V600E and Epidermal Growth Factor Receptor (EGFR) in Ameloblastoma - Bashir, Namrah; Asif, Muhammad; Malik, Iqraa Shakeel; Araa, Nighat; Rashid, Farhat; Uddin, Hafeez; Bashir, Aieman; Shakeel Malik, Numrah (Asian Pacific Journal of Cancer Biology, 2022)
Objective: To determine the Immunohistochemical expression of BRAF V600E and Epidermal growth factor receptor (EGFR) in ameloblastoma and correlate the expression with age and gender of patients, and patterns and types of ameloblastoma. Material & Methods: 39 cases were retrieved with their formalin-fixed, paraffin embedded blocks, trimmed and cut into 5 microns sections. They were mounted on slides after staining with routine hematoxylin and eosin followed by Immunohistochemical staining of BRAF V600E and EGFR. Mean and standard deviation were calculated for quantitative variables. Frequency and percentages were calculated for qualitative variables. Chi-square test was employed to assess the significance of difference. The p-value ≤ 0.05 was considered significant. Results: There were 19 (41.2%) males and 20 (48.7%) female patients. The mean age of patients at which they presented was 39.97 ± 15.505 (mean ± SD) with an age range between 12 to 65 years. 25 (64.1 %) cases showed positive expression of BRAF V600E and 14 (35.8 %) cases showed negative expression of BRAF V600E. 27 (69.2 %) cases showed positive expression of EGFR whereas 6 (15.3 %) cases showed negative expression of EGFR. The p-value was ≤ 0.05 for expression of BRAF V600E with respect to patterns of ameloblastoma and tumor site and expression of EGFR with respect to sub-types of ameloblastoma. Conclusion: There is positive expression of BRAF V600E (64.1%) and EGFR (74.4%) in different sub-types and patterns of ameloblastoma. Correct assessment with the help of these markers can lead to early diagnosis and use of adjuvant treatment protocols